Penggunaan Metode Proyek Untuk Mengembangkan Kemampuan Kerjasama Pada Anak Kelomok A di TK Widyapura Laweyan Surakarta - Nuria, Ratri (?ALI?A, 2018)
This study aimed to develop a social competent speciallycooperative learning at children for 4-5 age in TK WIDYAPURA. This studyincludes action research. Subject that was researched A groub ofkindergarten. Data has been collected for this research is child’s data andteacher’s data. Child’s data is observation about cooperative competent byproject method, while teacher’s data is observation of learning by projectmethode. The Result of reseach for every cycle is increasingly before of actionresearch is 40%, and after action research for cycle I is 67,2%, cycle II is88,9% and cycle III is 92,7%. Based on Result of this research is projectmethode can develop cooperative competent at children.